THE ROLE AND PROSPECTS OF TEACHING MATHEMATICAL MODELING IN THE DIGITAL LEARNING ENVIRONMENT OF HIGHER EDUCATION - Narzullayeva, Feruza; Khusniddin Jurayev (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the content and pedagogical approaches of the